Investigations into the complexity and polymorphism of HLA-D loci in South Africa - Oudshoorn, Machteld (Department of Clinical Laboratory Sciences, 2017)
The HLA complex is the most polymorphic genetic system known in man. The frequency of the HLA class II antigens have been well studied in Caucasoids but little data is available concerning HLA antigen frequencies in Negroes. In this thesis the class II antigens, excluding HLA-DP, were studied in South African (SA) Negroes (Xhosa), Cape Coloureds ( a group of mixed racial origin) and SA Caucasoids using serological, cellular ( HTC typing) and Southern blot techniques. The results obtained for the SA Negroes were compared with those previously found in Nigerians and American Negroes. Marked differences in HLA distribution occurred between these groups, which in part may be explained by Khoisan admixture in the SA Negroes. In addition, striking frequency differences were observed between the three SA populations. For example, in the Xhosa the HLA-DR1, DR4, DR7, DRw8, DQw2, DQw3, Dw1 and Dw3 specificities were found at a significantly lower frequency, whereas HLA-DR3, DRw6 and Dw' RSH' were found at a significantly higher frequency compared with the SA Caucasoids. The frequency in the Cape Coloureds was intermediate between those of the Xhosa and Caucasoids. In the SA Negroes and Cape Coloureds, several new specificities were detected such as HLA-DRw18, DR2 LUM(CT), DRwl2x6, DRw8x14, Dw' RSH', Dw' JOH' and Dw' BME'. The HLA-DR and DQ haplotypes in significant linkage disequilibrium were similar in the three groups. However, several haplotypes with unusual DR and DQ combinations such as HLA-DRw17,DQw7; DR9, DQw2 and DR4, DQw5 were present in the SA Negroes and Cape Coloured families. Al though some of these unusual haplotypes could be explained in terms of recombination between the common haplotypes, none could be typed using a panel of well defined homozygous typing cells, suggesting that the response observed in mixed lymphocyte culture arises from separate molecular determinants. The data on HLA class II antigen frequencies presented in this thesis is essential for future studies on HLA and disease associations and for establishing population relationships. Knowledge of new HLA class II antigens in the various population groups is also important in renal transplantation as matching for HLA-DR antigens is known to improve graft survival.